Sensing characteristics of conductance sensor for measuring the volume fraction and axial velocity in oil-water pipe flow. (1st January 2012) - Yingwei, Li; Xiaoming, Li
The output response characteristics, spatial sensitivity distribution, spatial filtering effect and frequency response characteristics are important parameters influencing the accuracy of conductance sensor for measuring the volume fraction and axial velocity in oil-water pipe flow. In this paper, the mathematical model of conductance sensor was established, and using the finite element analysis software ANSYS the finite element model was obtained. The analysis of output response characteristics of the sensor was performed with reference to different non-uniform mediums. The spatial sensitivity distribution was also investigated, and its spatial filtering effect was analysed quantitatively. On this basis the frequency response characteristics function was derived. With the optimised six-electrode conductance sensor, a two-phase flow measurement system was designed for oil well logging; and the experiments were performed. The results indicate that the measurement error of water volume fraction is ±3%, and the flow axial velocity can resolve the flowrate difference with 2 m 3 /d.